Justiça e inteligência artificial : algoritmos e resolução de conflitos - Camargo, Guilherme Affonso Ferreira de (2023)
This work explores the relationship between technology and justice, with a specific focus on the debate surrounding the use of algorithms in judicial proceedings as a replacement for human judges. It begins by establishing a definition of justice as a means of resolving conflicts and promoting harmonious coexistence in society. The discussion delves into the perspectives of essentialism and functionalism regarding the substitution of human tasks by machines. Essentialist arguments center on the absence of essential human properties that make it impossible for machines to replicate the outcomes of human work, while functionalists see no impediments to such substitution. The dissertation then examines the argument that the lack of creativity in artificial intelligence poses a limitation to its application in non-mechanical tasks. Essentialists associate creativity with consciousness, suggesting a biological component is necessary for machines to be considered creative, while functionalists focus on the outcome of activities, allowing for the attribution of creativity to machines. Furthermore, the paper delves into the implications of delegating judgments to machines, drawing upon the concept of legal realism. The concerns raised against machine substitution appear to be more related to a fear of losing control over technology rather than rejecting its benefits. The implementation of technology has already demonstrated efficiency in the resolution of conflicts, aligned with previous judgments. In light of these discussions, the work concludes that adopting na intermediate position, rather than embracing extreme rejection or uncritical adoption of technology, seems more appropriate. This approach acknowledges both technological advancements and a critical perspective on potential problems. It emphasizes the need to strike a balance, ensuring that justice is effectively achieved and fosters harmony in society. Ultimately, the amount of AI utilization in the judicial system remains a decision for humans to evaluate and supervise. Trade-offs between efficiency and satisfaction with the chosen conflict resolution system must be carefully considered. Incorporating AI into the judicial process requires an informed and ethical approach, considering the fundamental principles of justice and societal aspirations. By doing so, a well-balanced integration of technology and preservation of essential legal values can be achieved, contributing to the establishment of a just and harmonious society. This abstract was generated by an artificial intelligence after being provided with the entirety of the text.